Prevalence and factors associated with seizures among patients with dementia: A retrospective clinic‐based study - Liz Edenberg Quiles; Prima Kristina Paola Quintay; Adrian Espiritu; Viel Mendoza; Veeda Michelle Anlacan (Epilepsia Open)
Abstract Objective Chronic diseases associated with aging, such as dementia and seizures, are expected to rise significantly in the Philippines' growing elderly population. This study aims to determine the frequency, demographic characteristics, and clinical profile of dementia patients who developed new‐onset seizures in an outpatient setting. Methods This descriptive, retrospective, cumulative prevalence study included 245 patients diagnosed with dementia at a tertiary hospital in Manila from February 2010 to February 2020, according to DSM‐5 criteria. Patients were stratified into those who developed seizures and those who did not. Data on demographics, type, dementia severity, comorbidities, and seizure characteristics were collected and analyzed using descriptive statistics, bivariate, and multivariate logistic regression analyses. Results The study included 245 dementia patients, of whom 10 (4.1%) developed seizures, with a higher likelihood observed in those with severe dementia. Most patients were diagnosed with Alzheimer's disease, and seizures were mostly seen in individuals between the ages of 65 and 79. The majority of the seizures were classified as generalized (50%). Compared to mild cases, patients with moderate dementia are about 1.5 times more likely to experience seizures, whereas patients with severe dementia are about 10 times more likely to experience seizures compared to patients with mild dementia. The association is statistically significant for severe cases of dementia. Significance This study revealed that 4.1% of Filipino patients diagnosed with dementia in an outpatient setting at a tertiary hospital developed new‐onset seizures. Seizures were mostly reported in patients with severe Alzheimer's disease. Conventional understanding of seizures among patients with dementia is important to identify features and predictors to provide efficient management among these patients to possibly improve their quality of life. Plain Language Summary With the aging Filipino population, there is an expected rise in chronic diseases such as dementia and seizures. This study looked at dementia patients in an outpatient setting over 10 years and found that 4.1% developed seizures. Most patients had Alzheimer's disease, and seizures were more common in severe dementia cases.